Eksplorasi Kebudayaan Nagari Sikilang Sas: Menelusuri Tradisi, Kearifan Lokal dan Sosial - Hambali; Sutopo, Nur Fhadilla Alfanissa; Singgalan, Muhammad Arga; Pratiwi, Erin Cahya; Anihsa (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
Real Work Lecture (KKN) represents a tangible embodiment of the responsibilities attributed to both educators and students in the execution of the Tri Dharma of Higher Education, specifically concerning the dimension of community service. The initiatives undertaken by KKN Universitas Negeri Padang in Di Nagari Sikilang, West Pasaman Regency exemplify one of the manifestations of community engagement endeavors. The Real Work Lecture transpired from June 27, 2024, to June 27, 2024. Culture encompasses an intricate system of values, norms, knowledge, beliefs, and practices that fundamentally shape the lifestyle of a community. It incorporates local customs, traditions, and ancestral wisdom that are transmitted across generations. Culture is not limited to rituals and traditions; it also encompasses the interactions individuals have with their environment, the formation of identity, and the conduct of everyday life. In Nagari Sikilang, Pasaman Regency, West Sumatra, the rich heritage of Minangkabau culture is meticulously preserved through indigenous customs, traditions, and wisdom. This research investigates the structures and ceremonies associated with customs, religious practices, and local wisdom, illustrating the ongoing preservation of ancestral values. The study employs a qualitative methodology through direct observation and fieldwork conducted by KKN students. The findings underscore the significance of cultural preservation as an integral component of the identity and diversity inherent within the Indonesian nation.